Characterizing Disease and Outcomes in Intestinal Obstruction: A Retrospective Study in a Tertiary Center of Chitwan, Nepal - Bhujel, Sushim; Timilsina, Binaya; Pradhan, Saroj Babu; Khatiwada, Sagar; Shrestha , Sandesh; Ghimire, Rupak; Belbase, Narayan Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Intestinal obstruction is a major surgical emergency requiring timely intervention to minimize morbidity and mortality. While conservative management can be successful in select cases, delay in surgical intervention can lead to poor outcomes. Methods A retrospective descriptive study was conducted at the Department of Gastrointestinal and General Surgery, College of Medical Sciences Teaching Hospital, Bharatpur, Nepal. Data from October 2022 to October 2024 were analyzed. Eighty-five patients diagnosed with intestinal obstruction were included. Patient demographics, etiology, treatment approaches, and outcomes were analyzed using SPSS version 16.0. Results The most common etiology of intestinal obstruction was adhesive bowel obstruction(ABO) (38.82%), followed by hernias (17.65%) and malignancies (10.58%). Conservative management was attempted in 40 cases (47.05%), with a success rate of 55%. Patients requiring surgery upfront (45 cases, 52.94%) primarily had signs of strangulation, ischemia, or peritonitis. Laparoscopic adhesiolysis was performed in 14 cases, demonstrating shorter hospital stays (6 ± 1.5 days) compared to open surgery (7 ± 3 days). Postoperative complications included surgical site infections (24.59%) and ileus, with a 30-day mortality rate of 3.36%. Conclusions The study emphasizes that the most frequent cause of intestinal obstruction is still Adhesive bowel obstruction. Conservative management is feasible for a substantial proportion of intestinal obstruction cases; however, a significant percentage require surgical intervention. Furthermore, this study shows that laparoscopic surgery has the potential to improve patient outcomes and sheds light on whether it is a feasible alternative for a subset of ABO patients.